2021
DOI: 10.3390/w13233390
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Runoff Forecasting Model Based on the Decomposition-Integration-Prediction Framework

Abstract: Runoff forecasting is of great importance for flood mitigation and power generation plan preparation. To explore the better application of time-frequency decomposition technology in runoff forecasting and improve the prediction accuracy, this research has developed a framework of runoff forecasting named Decomposition-Integration-Prediction (DIP) using parallel-input neural network, and proposed a novel runoff forecasting model with Variational Mode Decomposition (VMD), Gated Recurrent Unit (GRU), and Stochast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 56 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…The electricity load sequence data have non-stationary and non-linear characteristics, and the load data is preprocessed by VMD [29,30]. By iteratively searching for changing modes, the VMD decomposes the original load series into several mode components with finite bandwidth [31], as shown in Equation (1).…”
Section: Decomposition and Reconstruction Of Load Datamentioning
confidence: 99%
“…The electricity load sequence data have non-stationary and non-linear characteristics, and the load data is preprocessed by VMD [29,30]. By iteratively searching for changing modes, the VMD decomposes the original load series into several mode components with finite bandwidth [31], as shown in Equation (1).…”
Section: Decomposition and Reconstruction Of Load Datamentioning
confidence: 99%
“…Te results indicated that VMD decomposition could remove the interference noise in the data and improve the robustness of the model. In order to reduce noise, Xu and Yan et al [32,33] applied VMD to food data preprocessing. Experimental results showed that VMD decomposition could remove the interference noise in the water level data and improve the signal-to-noise ratio, further combining with the deep learning neural network algorithm to improve the food prediction accuracy [33].…”
Section: Introductionmentioning
confidence: 99%
“…In runoff prediction, the GRU model has shown superior performance compared to the SVM model, with further enhancement in prediction accuracy observed upon incorporating sequence processing technologies [15]. For instance, the RMSE of the DWT-GRU model decreased in comparison to the single GRU model [16]; the VMD-GRU model exhibited higher prediction accuracy than the standalone GRU model for monthly runoff prediction [17]; and the CEEMDAN-FE-VMD-SVM-GRU model outperformed eight other models for the daily runoff prediction [18]. Additionally, identifying the optimal combination of input variables, typically involving rainfall and runoff measurements [19], for a DWT-VMD-GRU runoff model is crucial.…”
Section: Introductionmentioning
confidence: 99%